The Mathematical modelling of the SIR-SI contagion model of dengue disease which considers the blood type O factor human compartment : A theoretical simulation - Nor Azah Samat (Tanjong Malim, 2019)
The Mathematical modelling of the SIR-SI contagion model of dengue disease which considers the blood type O factor human compartment : A theoretical simulation by Nor Azah Samat